PENDIDIKAN ANTISIPATORIS DALAM MENGHADAPI ARUS TRANSFORMASI DUNIA PADA NOVEL SOKOLA RIMBA KARYA BUTET MANURUNG - Rian Aji Lestari; M Shoim (Universitas PGRI Adi Buana Surabaya, 2015)
Abstract This research is motivated by less inequality in rights education for all citizens of Indonesia. Differences in customs, ethnicity, race, religion, and social class made as demarcation to recognize education. These conditions make room for the presence of various forms of oppression. The research objective is to provide an understanding of the importance of education for life. Education will bring someone in better condition. The method used is qualitative method. Research with qualitative methods is the researcher's own instrument, prioritizing the provision of theory and extensive knowledge thus, able to analyze and construct the social situation under study becomes more clear and meaningful. In this study, the research focus lead to five points. The first is the belief traditions in education restraint. The second is to change the mindset and planting awareness education. Third is the suppression of the right of freedom for the people of the jungle. Fourth was the sinking of education for one gender. Fifth is anticipatory education in the face of the current world transformation. That's five things into the realm of research on novel Sokola Rimba by Butet Manurung. Key Words: Education, transformation, customs.